The wax bloom on blueberry: Application of luster sensor technology to assess glossiness and the effect of polishing as a fruit quality parameter - Patiwit Loypimai; Sudpiti Paewboonsom; Lutz Damerow; Michael M. Blanke (Journal of Applied Botany and Food Quality, 2017)
The wax bloom of the fruit is responsible for the visible quality of blueberries. This study aimed to investigate a new technology using the effect of polishing on micromorphology, wax content and weight loss of blueberries. Luster sensor (type CZ-H72, Keyence, Japan) technology was used to assess glossiness of polished blueberries compared with berries with a natural (unpolished) wax layer during 9 days after harvest. Blueberries were rubbed twice by hand within a soft microfibre tissue to obtain polished fruit. Unpolished blueberries contained ca. 120 μg wax cm-2, which was reduced by ca. 22% to ca. 95 μg cm-2 by polishing. This reduction was associated with an increase in luster levels from ca. 65 to 80 a.u.. Weight loss was larger from polished than from unpolished blueberries with a concomitant 40% increase in luster levels from 60 to 85 a.u. in polished fruit. Luster levels sharply decreased from 85 a.u. in the first 5 days after harvest and then leveled off to remain almost constant at ca. 20 a.u. with significantly larger values for polished blueberries of ca. 30 a.u. with a larger magnitude of glossiness. Overall, luster sensor technology may offer a new effective, affordable, possibly portable, non-destructive technique to assess glossiness or other surface features in real time for classifying not only blueberry, but also other waxy fruit such as aubergine/eggplant, plum, Juniperus, blue grape berry etc..